Aortic Gene Expression Profiles Show How ApoA-I Levels Modulate Inflammation, Lysosomal Activity, and Sphingolipid Metabolism in Murine Atherosclerosis. Issue 2 (February 2021) - Busnelli, Marco; Manzini, Stefano; Chiara, Matteo; Colombo, Alice; Fontana, Fabrizio; Oleari, Roberto; Potì, Francesco; Horner, David; Bellosta, Stefano; Chiesa, Giulia
Abstract : Objective: HDL (high-density lipoprotein) particles are known to possess several antiatherogenic properties that include the removal of excess cholesterol from peripheral tissues, the maintenance of endothelial integrity, antioxidant, and anti-inflammatory activities. ApoA-I overexpression in apoE-deficient (EKO) mice has been shown to increase HDL levels and to strongly reduce atherosclerosis development. The aim of the study was to investigate gene expression patterns associated with atherosclerosis development in the aorta of EKO mice and how HDL plasma levels relate to gene expression patterns at different stages of atherosclerosis development and with different dietary treatments. Approach and Results: Eight-week-old EKO mice, EKO mice overexpressing human apoA-I, and wild-type mice as controls were fed either normal laboratory or Western diet for 6 or 22 weeks. Cholesterol distribution among lipoproteins was evaluated, and atherosclerosis of the aorta was quantified. High-throughput sequencing technologies were used to analyze the transcriptome of the aorta of the 3 genotypes in each experimental condition. In addition to the well-known activation of inflammation and immune response, the impairment of sphingolipid metabolism, phagosome-lysosome system, and osteoclast differentiation emerged as relevant players in atherosclerosis development. The reduced atherosclerotic burden in the aorta of EKO mice expressing high levels of apoA-I was accompanied by a reduced activation of immune system markers, as well as reduced perturbation of lysosomal activity and a better regulation of the sphingolipid synthesis pathway. Conclusions: ApoA-I modulates atherosclerosis development in the aorta of EKO mice affecting the expression of pathways additional to those associated with inflammation and immune response. Abstract : Supplemental Digital Content is available in the text.